Thyroid Function Testing - Brent, Gregory A.; Brent, Gregory A. (Endocrine Updates, 2010)
Thyroid function tests are performed by essentially all medical practitioners across every clinical setting. Significant insights have been gained into thyroid regulation and thyroid hormone metabolism that influence the selection and interpretation of thyroid function tests. Recent studies are summarized showing that genetic variations in key thyroid regulating genes may influence thyroid function tests. The basics of thyroid function measurements, approaches, limitations and clinical applications will be described for the major categories of thyroid function tests. Application of thyroid function testing to key clinical settings are discussed, including management of thyroid diseases. An approach to thyroid function testing in special groups is described, including infants and children, the elderly, pregnant women, and the hospitalized patient. The authors represent leaders in research and clinical practice from world class centers of excellence in medicine. "In this volume, leading experts provide a comprehensive overview of a difficult and commonly encountered clinical challenge--how to interpret thyroid function test results. Ranging from fundamental genetics to both inpatient and outpatient environments, this book will be of enriching value to internists, pediatricians, endocrinologists and those studying thyroid physiology." - Shlomo Melmed, M.D. Series Editor.